Titanium alloy cannulated screws and biodegradable magnesium alloy bionic cannulated screws for treatment of femoral neck fractures: a finite element analysis - Kai Ding (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Cannulated screws (CS) are one of the most widely used treatments for femoral neck fracture, however, associated with high rate of complications. In this study, we designed a new type of cannulated screws called degradable magnesium alloy bionic cannulated screws (DMBCS) and our aim was to compare the biomechanical properties of DMBCS, the traditionally used titanium alloy bionic cannulated screws (TBCS) and titanium alloy cannulated screws (TTCS). Methods A proximal femur model was established based on CT data of a lower extremity from a voluntary healthy man. Garden type III femoral neck fracture was constructed and fixed with DMBCS, TBCS, and TTCS, respectively. Biomechanical effect which three type of CS models have on femoral neck fracture was evaluated and compared using von Mises stress distribution and displacement. Results In the normal model, the maximum stress value of cortical bone and cancellous bone was 76.18 and 6.82 MPa, and the maximum displacement was 5.52 mm. Under 3 different fracture healing status, the stress peak value of the cortical bone and cancellous bone in the DMBCS fixation model was lower than that in the TTCS and TBCS fixation, while the maximum displacement of DMBCS fixation model was slightly higher than that of TTCS and TBCS fixation models. As the fracture heals, stress peak value of the screws and cortical bone of intact models are decreasing, while stress peak value of cancellous bone is increasing initially and then decreasing. Conclusions The DMBCS exhibits the superior biomechanical performance than TTCS and TBCS, whose fixation model is closest to the normal model in stress distribution. DMBCS is expected to reduce the rates of post-operative complications with traditional internal fixation and provide practical guidance for the structural design of CS for clinical applications.